Types and typifications of some names published for ferns and lycophytes endemic to São Tomé and Príncipe - Figueiredo, Estrela; Smith, Gideon F. (Phytotaxa, 2024)
The typification of the currently accepted names of 14 pteridophytes, i.e., ferns and lycophytes, which are definitely endemic to São Tomé and Príncipe, is reviewed. Lectotypes are designated for a number of names and previous typifications are reassessed and corrected, if needed. The types of the names of three further pteridophytes, one endemic to the Gulf of Guinea and two widespread ones, are also discussed.